INDUSTRI PERBANKAN YANG TERKONSENTRASI APAKAH TETAP DAPAT BERKOMPETISI? KASUS PERBANKAN SYARIAH - Sancoko Sancoko (Jurnal Vokasi Indonesia, 2013)
ABSTRACT -This paperdiscusses theconditions ofcompetitionbankingindustryin Indonesia, especiallyIslamicBankingentity. Islamic Bankbecame the objectof research because significant growth in industrial banking.Thisstudyuses a quantitative approachwith adescriptivedesign. Source ofdata used fromindividualbank's annualreporton the websiteof BankIndonesia fromthe period 2008-2011. Tomeasureaspects ofcompetition IslamicBankingusing Panzar&Rosestatisticmethods. Results of studyshowed thatIslamic banking came into conditionof monopolisticcompetitition structure.Keywords: